2011
DOI: 10.1017/s1463423611000193
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of acute upper respiratory tract infections in children

Abstract: Diaries were returned from 223 children, of whom 146 had had an AURI. The average age was eight years, and there were almost equal numbers of boys and girls. The most frequent symptoms were runny nose, cough, feeling unwell and sore throat. There was a biphasic distribution with systemic symptoms in the first three days characterised by fever, poor sleep, irritability, not playing and headache. By day four, symptoms localising the infection to the upper respiratory tract appeared with runny nose, cough, sore t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 5 publications
0
30
0
Order By: Relevance
“…In the current study, the 2‐wk definition for rhinitis based on the ARIA guideline which states that symptoms lasting for more than 2 wk should be investigated for a cause aside from infection . This recommendation was substantiated in a recent study which observed that upper respiratory infection in children rarely lasted beyond 14 days . In addition, it can be difficult for parents to exclude symptoms due to cold or the flu (ISAAC definition) in this age group as seen in the high rate of positive responses (42.7%) in a cross‐sectional study performed on children <2 yr of age in our population , most likely an overestimation of the true prevalence of rhinitis.…”
Section: Discussionmentioning
confidence: 82%
“…In the current study, the 2‐wk definition for rhinitis based on the ARIA guideline which states that symptoms lasting for more than 2 wk should be investigated for a cause aside from infection . This recommendation was substantiated in a recent study which observed that upper respiratory infection in children rarely lasted beyond 14 days . In addition, it can be difficult for parents to exclude symptoms due to cold or the flu (ISAAC definition) in this age group as seen in the high rate of positive responses (42.7%) in a cross‐sectional study performed on children <2 yr of age in our population , most likely an overestimation of the true prevalence of rhinitis.…”
Section: Discussionmentioning
confidence: 82%
“…A negative association exists between age and the frequency of episodes and the duration of the symptoms . In children, most symptoms disappear by day 7, with occasionally, a cough and runny nose continuing for up to 20 days …”
Section: Introductionmentioning
confidence: 99%
“…The longest cough duration in this study was 21 days and initially more than 50% of parents described the cough as dry with the remainder reporting the cough to be productive or of a mixed type. Recently Mitra et al followed the course of acute URTI in children and reported cough to be the second commonest symptom to runny nose occurring in more than 80% of children [4]. The coughing occurred after an initial 1–2 days of systemic illness with fever and a feeling of un-wellness.…”
Section: Prolonged Acute Coughing In Childrenmentioning
confidence: 99%